FACTORS AFFECTING THE VISUAL INSPECTION OF ACETIC ACID EXAMINATION (IVA) IN PADANG CITY 2019 - Lusiana El Sinta B; Laila Rahmi; Uliy Iffah (Universitas Andalas, 2020)
Cervical cancer is the fourth most common cancer in women with a mortality rate of 6.8% (WHO, 2015; Globocan, 2012). The incidence of cervical cancer ranks second after breast cancer in Southeast Asia and Indonesia. Based on data from the Republic of Indonesia Ministry of Health 2015, cervical cancer is the cancer with the highest prevalence of 0.8 per 1000 population (Ministry of Health Republic of Indonesia, 2015). The high prevalence of cancer in Indonesia requires prevention and early detection by health service providers. The purpose of this study was to determine the factors that influence the inspection of Acetic Acid Visual Inspection (IVA) in Padang City.This type of research is quantitative with cross sectional design. The study was conducted at the Padang City Health Center in April-November 2019. The population was all women aged 30-50 years who were at the Padang City Health Center, amounting to 10,670 people, with a sample of 73 people taken by consecutive sampling technique. Data were collected by questionnaire and analyzed by univariate and bivariate analysis.More than half (64.4%) of women of childbearing age (WUS) have never had an IVA examination, more than half (58.9%) of women have a risk age, less than half (39.7%) women have low levels of education , more than half (60.3%) WUS with working status, there was no relationship between the age of WUS with IVA examination (p value = 0.182), there was a relationship between WUS education level and IVA examination (p value = 0.031), there was no relationship between the status of WUS work and IVA examination (p value = 0.404). It is expected that officials and leaders of puskesmas will develop more attractive ways to be able to convince and increase awareness and concern of the WUS themselves in conducting IVA examinations.